Empowering Local Economies: The Strategic Role of Small and Medium Enterprises in Driving Sustainable Growth - Adinda, Adinda; Akbar Budiman, Muhammad (Jurnal Inovasi Ekonomi, 2025)
This study aims to analyze the role of Small and Medium Enterprises (SMEs) in promoting local economic growth. Using a literature review approach, this research provides a comprehensive overview of SMEs’ contributions to job creation, income generation, and the enhancement of regional economic competitiveness. The findings indicate that SMEs play a crucial role not only as providers of goods and services but also as key drivers in expanding market access and fostering employment opportunities. However, SMEs face several challenges, including limited access to capital, technological constraints, and inadequate managerial capacity. The study highlights the importance of government support through policy frameworks, financial assistance, and capacity-building programs to strengthen SME performance. Ultimately, this research emphasizes that optimizing the role of SMEs can significantly contribute to sustainable local economic development and inclusive growth.